Behavior of layered double hydroxides having different divalent transition metal groups - Mamat M.; Tagg T.; Khairul W.M.; Abdullah M.A.A.; Mohd Tahir N.; Jubri Z.; As'ari R.A. (Trans Tech Publications, 2023)
The layered double hydroxides (LDHs) with different divalent transition metal groups and nitrate as a counter anion were investigated. Three d-block divalent metals namely cobalt (Co), nickel (Ni) and copper (Cu) were selected. The cobalt/aluminium (CoAN)-, nickel/aluminium (NiAN)- and copper/aluminium (CuAN)-layered double hydroxides were successfully synthesized via coprecipitation method. All the obtained LDHs were characterized by PXRD, FT-IR, ICP-OES, CHNS and TGA/DTG analysis. Interestingly, behavior of the LDHs was dependent on the size of divalent cations. PXRD showed the basal spacing decrease in the order NiAN (0.88nm)> CuAN (0.87nm) > CoAN (0.74nm), and in a linear correlation with the increasing radii of the divalent cations. Similar trend is observed for the weight loss of LDHs, where NiAN has the highest weight loss (53%), followed by CuAN (43%) and CoAN (34%). Further elemental analysis showed the content of trivalent metal cations, nitrate anions and water molecules in the LDHs decrease with the increasing radii. © (2014) Trans Tech Publications, Switzerland.